Bridging the Gap Between Community Schools and Rural Communities in Nepal Using Participatory Action Research - Shrestha, Salpa; Raj Dangal, Megh (Australian and International Journal of Rural Education, 2024)
This paper explores the engagement of parents with out-of-school children through community-based participatory action research in a rural community in Nepal. This study addresses the connection gap between local communities and community schools, which has resulted in consequences such as inconsistent attendance among students and low educational expectations among parents. By investigating the processes of formulating an action plan by a parent-led action group and analysing its execution, the research aimed to understand how participatory action research can foster a stronger bond between community schools and parents, thereby enhancing parental involvement in children’s education. The study draws on Mezirow’s transformative learning theory, incorporating concepts from Habermas’s public sphere and Freire’s notion of conscientization. It specifically focuses on the action group’s monthly meetings held over nine months and the collaborative outcomes that resulted. By emphasising targeted interventions, collaboration and a departure from deficit-focused approaches, the findings propose effective strategies for bridging the gap between community schools and rural communities in Nepal.